In vitro models of breast cancer bone metastasis: analyzing drug resistance through the lens of the microenvironment - Lamouline, Anaïs; Bersini, Simone; Moretti, Matteo (Frontiers in Oncology, 2023)
Even though breast cancers usually have a good outcome compared to other tumors, the cancer can progress and create metastases in different parts of the organism, the bone being a predilection locus. These metastases are usually the cause of death, as they are mostly resistant to treatments. This resistance can be caused by intrinsic properties of the tumor, such as its heterogeneity, but it can also be due to the protective role of the microenvironment. By activating signaling pathways protecting cancer cells when exposed to chemotherapy, contributing to their ability to reach dormancy, or even reducing the amount of drug able to reach the metastases, among other mechanisms, the specificities of the bone tissue are being investigated as important players of drug resistance. To this date, most mechanisms of this resistance are yet to be discovered, and many researchers are implementing in vitro models to study the interaction between the tumor cells and their microenvironment. Here, we will review what is known about breast cancer drug resistance in bone metastasis due to the microenvironment and we will use those observations to highlight which features in vitro models should include to properly recapitulate these biological aspects in vitro. We will also detail which elements advanced in vitro models should implement in order to better recapitulate in vivo physiopathology and drug resistance.